PENYULUHAN DAN BAKTI SOSIAL PEMANFAATAN DAUN UBI JALAR TERHADAP PRODUKSI ASI - Sutrani Syarif; Ani T Prianti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2022)
Some residents, sometimes use herbal plants to treat perceived health complaints, but their utilization is not optimal because so far the use of traditional medicinal plants is only based on the opinions of friends or neighbors and hereditary traditions. The use of traditional medicine that is not in accordance with the rules, is feared to reduce the efficacy of the drug itself. If the use is too much, it is feared that it will also have a toxic effect that will be dangerous for the community. For this reason, it is necessary to educate the public, so that the utilization of family herbal plants can be optimal, and the health status of the community increases. Sweet potato leaves can also increase milk production because in the sweet potato leaves there are galactagogue substances that can increase breast milk production so that they can meet the nutritional needs of babies through breast milk. The socialization activity was carried out on Wednesday, February 16, 2022 at 09.00 WITA, located in Tanakaraeng Village, Manuju District, Kab. Gowa. This activity aims to provide information to the public about various plants that have efficacy as herbal plants, how to use herbal plants, especially for obstetric services, which includes how to use, process and dose/dose herbs. This educational process uses a lecture method with the help of powerpoints and leaflets.